2004
DOI: 10.1128/jb.186.17.5640-5648.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilisLmrA Is a Repressor of thelmrABandyxaGHOperons: Identification of Its Binding Site and Functional Analysis oflmrBandyxaGH

Abstract: The Bacillus subtilis lmrAB operon is involved in multidrug resistance. LmrA is a repressor of its own operon, while LmrB acts as a multidrug efflux transporter. LmrA was produced in Escherichia coli cells and was shown to bind to the lmr promoter region, in which an LmrA-binding site was identified. Genome-wide screening involving DNA microarray analysis allowed us to conclude that LmrA also repressed yxaGH, which was not likely to contribute to the multidrug resistance. LmrA bound to a putative yxaGH promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…Finally, the organization of breR with respect to breAB represents a novel arrangement for these systems, since the genes that encode TetR regulators that control the expression of the cognate genes encoding RND efflux systems are localized either in a divergent orientation adjacent to the genes they regulate (1,17,31,35) or in the same operon (39,53). In contrast, breR is located 8.99 kb upstream, positioned several genes away from the breAB operon.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the organization of breR with respect to breAB represents a novel arrangement for these systems, since the genes that encode TetR regulators that control the expression of the cognate genes encoding RND efflux systems are localized either in a divergent orientation adjacent to the genes they regulate (1,17,31,35) or in the same operon (39,53). In contrast, breR is located 8.99 kb upstream, positioned several genes away from the breAB operon.…”
Section: Discussionmentioning
confidence: 99%
“…Increased transcription also results in overexpression of the MDT. Puromycin-and lincomycin-resistant (PLR) mutants, isolated by growing B. subtilis 168 in the presence of high concentrations of puromycin and lincomycin, display increased expression of LmrB because of the inactivation of a negative transcriptional regulator, LmrA, or because of mutations in the 5Ј untranslated region (5Ј UTR), which is a binding site for the LmrA protein (16,25). Expression of Bmr and Blt is regulated by the product of adjacent genes encoding the transcriptional activators BmrR and BltR, respectively (1,2).…”
mentioning
confidence: 99%
“…With the combination of DNA microarray analysis and genome-wide computational sequence analysis, another LmrA target, yxaGH, was identified, which was found in the putative yxaGH promoter region two tandem LmrA-binding cis sequences, each of which is similar to that in the lmrAB promoter region (30). However, the DNA binding of LmrA was not inhibited by lincomycin, with the inducer interacting with LmrA remaining to be identified (30). Besides these findings, it was reported that yxaG encodes quercetin 2,3-dioxygenase, which is involved in flavonol degradation (3), whereas yxaH encodes a membrane protein of unknown function.…”
mentioning
confidence: 99%